Amoebic gill disease (AGD)-affected Atlantic salmon, Salmo salar L., are resistant to subsequent AGD challenge - Vincent, BN; Morrison, RN; Barbara Nowak (2006)
There is inconsistent evidence of resistance of Atlantic salmon, Salmo salar L., to amoebic gill disease (AGD). Here, evidence is presented that demonstrates that Atlantic salmon exposed and subsequently challenged with AGD are more resistant than naïve control fish. Seventy-three per cent of Atlantic salmon previously exposed to AGD survived to day 35 post-challenge compared with 26% exposed to Neoparamoeba sp. for the first time, yet the gill pathology of surviving naïve control or previously exposed fish was not significantly different. Development of resistance to AGD is associated with anti-Neoparamoeba sp. antibodies that were detectable in serum of 50% of surviving Atlantic salmon previously exposed to AGD. However, anti-Neoparamoeba sp. antibodies were not detectable in cutaneous mucus of resistant fish. Increased resistance of Atlantic salmon after secondary Neoparamoeba sp. infection and detection of specific serum antibodies provides support for the development of a vaccine for AGD. © 2006 Blackwell Publishing Ltd.